2015
DOI: 10.1089/vbz.2014.1758
|View full text |Cite
|
Sign up to set email alerts
|

BartonellaOsteomyelitis of the Acetabulum: Case Report and Review of the Literature

Abstract: Introduction: Bartonella henselae commonly involves the mononuclear phagocyte system (MPS), and its most common presentation is lymphadenitis. Rarely, it can cause isolated osteomyelitis. We present a case of a 3 year old with constitutional symptoms and new onset of limp. Previously reported cases of osteomyelitis due to B. henselae are also reviewed here, keeping the index case in mind. Methods: We conducted a Medline search using MeSH subject headings Bartonella and osteomyelitis, limited to humans. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
(9 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, while osteomyelitis caused by other common organisms mainly involves the legs [ 46 ], we found that the most affected bones during CSD are vertebral bodies followed by limbs [ 41 , 45 , 47 ]. Osteomyelitis of the skull is a rare manifestation with 10 cases in 50 years in the literature [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while osteomyelitis caused by other common organisms mainly involves the legs [ 46 ], we found that the most affected bones during CSD are vertebral bodies followed by limbs [ 41 , 45 , 47 ]. Osteomyelitis of the skull is a rare manifestation with 10 cases in 50 years in the literature [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCR involves amplification of Bartonella species genes (16S rRNA gene, citrate synthase gene (gltA), and htrA gene) directly from tissue or aspirate. It is specific but with a variable sensitivity (40–70%) with high risk of negative results if sample collection occurs too early (<6 weeks) [ 47 , 57 61 ]. PCR testing of the lymph node was not performed in our case since it is an invasive procedure and requires sedation in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bartonella henselae , a Gram-negative bacterium, is the causative agent of cat scratch disease (CSD) that typically involves the mononuclear phagocyte system and presents as local lymphadenopathy, often accompanied by fever [ 1 ]. B. henselae infections are thought to occur when a human is bitten or scratched by an infected cat [ 2 4 ] and may be transmitted by cat fleas or by an infected cat licking the nonintact skin of a human [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fever was present in 78% as part of their initial presentation, and most cases involved the axial skeleton. [ 4 ],[ 5 ] Since 2007, skull involvement was noted in just 1 of the 14 cases reported by Puri et al . [ 5 ] The frontal bone, parietal bone, and mastoid bone have all been reported to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of Bartonella osteomyelitis is poorly understood, but both direct extension from infected lymph nodes (contiguous infection) and distant infection (presumably from hematogenous or lymphohematogenous spread) have been reported. [ 4 ],[ 5 ],[ 7 ] Eight of the 14 cases reported by Puri et al . tested positive for Bartonella by PCR at the site of the infection.…”
Section: Discussionmentioning
confidence: 99%